Garden of shadows - Andrews, V. C. (Virginia C.) (Dollanganger Family., 1987)
Relating the events that led to those in the horror series that began with "Flowers in the Attic," this novel introduces the young, dashing Malcolm Foxworth and his new wife, Olivia, and reveals why they became evil.